The Card of the Pole: Evolution and Main Problems of Functioning in 2008–2021 - Czachor, Rafał (Teisė, 2022)
Many contemporary European countries have introduced legal instruments that are intended to establish and regulate the legal status of compatriots living abroad. In the Republic of Poland, a relevant act, “On the Card of the Pole,” was adopted in 2007. The following paper sheds a light on various issues regarding the scope of this bill, the subsequent amendments and the main problems of the functioning of this institution.
Keywords: administrative law; Poland; the Card of the Pole; national minority; the legal status of compartiots abroad